La perspectiva poliangular siqueiriana, como método de organización del espacio aplicada a la construcción de un mural en un edificio público de la ciudad de Loja - Carrión Yanangómez, Brayan Bolívar (2014)
The objective of the present research is to develop the technical artistic knowledge of the mural painting, taking as a reference the pluri-angular siqueiriana perspective, applied toward fulfillment of a mural, made on a public building of the Loja city. Transmitting ideas and knowledge into the work paintings, that has been remarkable into the history, due to a fundamental step of the art, for continuous innovations over the use of new techniques. The proposal has been established by the application of perspectives, with different topics, created and recreated among them to express the painting with a tridimensional effect using the multi-angles, where is organized the space between the painting and architecture interrelation. Through this manner, it is showed a good handling of the technique, likewise, it is deep into speech regarding to a cultural mythical topic of the contemporaneous society. The ideas and conceptions that will be done by the professor David Alfaro Siqueiros are relevant, due to his works that were applied on a paradigm of multi-angles. Therefore, it is noted the mural proposal achieves harmony, volume, and effects that allow the spectators enjoy the paintings, at the moment, they look at them.